Obstructive Renal Failure Caused by Bilateral Renal Candidiasis and Hypoplastic Renal Pelvises in a Preterm Infant: Case Presentation and Review of the Literature - Farhad Abolhassan Choobdar; Elham Zarei; Mohammad Reza Navaeifar; Ali Manafi Anari; Behzad Haghighi Aski (Mazandaran University of Medical Sciences, 2016)
Introduction Candida is one of the common causes of infections in late sepsis of very low birth weight neonates. The outcome ranges from a mild focal disease to a fatal septicemia and multi-organ dysfunction. Case Presentation Acute renal failure was found in a seven-week-old preterm infant due to bilateral renal fungal balls and hypoplastic renal pelvises. He had previously been treated with courses of broad-spectrum antibiotics for respiratory distress and sepsis during the first weeks of life. The infant did not respond to standard antifungal therapy and needed surgical removal of fungal balls from his kidneys, open nephrostomy tube placement and pyeloplasty. Conclusions Obstructive uropathy by fungal balls is rare and acute renal failure as a result of bilateral obstructive uropathy due to fungal balls requires early detection and prompt treatment to salvage the kidney function.